Islamic Religious Education and Deconstructing Prejudice: Strengthening Religious Moderation and Social Harmony Among Multicultural Students - Murdianto (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
Islamic Religious Education (PAI) plays an important role in fostering religious moderation among multicultural junior high school students. Moderation refers to a balanced religious attitude that avoids extremism, respects diversity, rejects violence, and promotes peaceful coexistence. This is particularly crucial during adolescence, when students are shaping their social and religious identities. Before implementing moderation-based learning, many students viewed religion in a formalistic way, focusing mainly on rituals rather than values like empathy, respect, and responsibility. They often judged peers based on outward differences, highlighting the need for value-oriented religious education. To address this, PAI teachers integrated moderation values into existing topics such as moral teachings, social ethics, and Islamic history. By linking lessons to real-life examples, including the coexistence of diverse communities in Medina, students gained a more practical understanding of religious values. As a result, positive changes emerged: students became more respectful, open to different opinions, more collaborative, and showed reduced conflicts, indicating stronger social harmony.